Mercury effect on embryonic development of Zebrafish - Carvalho, Inês de Almeida Mendes Marques de (2019)
Mercury (Hg) is a widespread contaminant hazardous to the environment and human health. Danio rerio (zebrafish) is a common model species used in toxicology and ecotoxicology, as a surrogate model to understand the effects of contaminants on human health and the environment. The aim of this study was to identify the effects of mercury (Hg) exposure on zebrafish embryo development and biomarkers levels. Zebrafish embryos were exposed to different concentrations of HgCl2 (0, 10 and 100 μg/L) up to 96 hours post-fertilization (hpf). Toxicity and developmental endpoints were assessed every 24h during the exposure period. Hg-induced alterations in the levels of Cholinesterase (ChE), Catalase (CAT), Glutathione-S-transferase (GST), Glutathione-Reductase (GR), Phosphoprotein Phosphatase-1-gamma (PPP1CC) and Glutathione Peroxidase-4 (GPx4), were assessed in zebrafish eggs or larvae, collected and snap-frozen prior to analysis every 24h up to 96h. Results showed that at 100 μg/L HgCl2 induced developmental changes in zebrafish development, including several malformations (eg. Pericardial edema and curvature) and delay of the hatching period. Additionally, a significant decrease in ChE levels (marker of neurotoxic damage) was detected in individuals exposed to 100 μg/L of HgCl2, while an increase in GST activity levels (marker of oxidative stress) was observed. For the first time, the effect of Hg on the levels of PPP1CC and GPx4 during zebrafish development was tested. Overall, we found levels of PPP1CC to increase over time. No alteration on protein levels following Hg exposure were, however, reported. Taken together, our study showed that Hg exposure induced alterations at developmental and biomarkers levels.